Design and Optimization of Static Characteristics for a Steering System in an ATV. Issue 1 (October 2020) - Rajeshkumar, L.; Bhuvaneswari, V.; Pradeepraj, B.; Praveen pauldurai, M.; Palanivel, C.; Sandeep kumar, S.
Abstract: The suspension and steering system of an ATV (All-Terrain Vehicle) plays a vital role in vehicle dynamics for off road conditions by load transfer and providing stability. Incorrect geometry and additional mass on the front axle affect the stability and performance of the vehicle in dynamic condition. This can be optimized by varying the geometric, design and mass characteristics of the wheel assembly and suspension system parameters. CAD model of the wheel assembly and steering gear box had been developed using SOLIDWORKS, with respect to geometric parameters obtained on suspension and steering system analysis using LOTUS software with various structural and geometric constraints. Finite element analysis of the wheel assembly was done using ANSYS WORKBENCH for static and basic dynamic loading conditions. Then topology analysis has been done to reduce the additional mass of the wheel assembly without compromising its geometric and load transfer characteristics.